Zolpidem and Zolpidem Carboxylic Acid Results from Medication Monitoring. Issue 7 (10th May 2018) - Feng, Sheng; Cummings, Oneka T; McIntire, Gregory
Abstract: Zolpidem (Ambien®) is one of the "Z" drugs often used to improve sleep in older patients and those suffering from insomnia. Schwope, D.M., DePriest, A., Black, D.L., Caplan, Y.H., Cone, E.J., Heltsley, R. (2014) Determing zolpidem compliance: urinary metabolite detection and prevalence in chronic pain patients . Journal of Analytical Toxicology, 38, 513–518 reported that zolpidem in urine is not very prevalent being present <23% of the time in patient urine while the major metabolite, zolpidem 4-phenyl carboxylic acid (ZCA), is much more prevalent in urine with positive rates as high as 50% of the patient samples reviewed. Results from patient testing over a year's time are in agreement with the reported zolpidem results. However, the data observed herein for ZCA are not consistent with the earlier report. These data suggest that monitoring ZCA may result in even higher levels of positivity. Further, while the Food and Drug Administration has pointed out that female dosing should be half that given to males, results of this population testing indicate that the majority of patients (83% male and 73% female) receive 10 mg/day or 12.5 mg/day for Ambien CR® with females demonstrating statistically significantly higher levels of ZCA albeit zolpidem levels are not statistically significantly different between men and women. Estimates of patient positivity are dependent upon the value of the limit of quantification (LOQ) as demonstrated by the zolpidem results herein (LOQ = 50 ng/mL vs. 4 ng/mL). However, even with a much higher LOQ of 50 ng/mL for ZCA in this work, the positivity from ZCA results is significantly higher (e.g., 64.8%) than reported earlier (50.3%). Nevertheless, these data support the addition of ZCA for monitoring zolpidem in urine.